2012
DOI: 10.4028/www.scientific.net/amm.232.614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Optimization Algorithm on Airfoil Shape Optimization of Aircraft Wings

Abstract: Computational fluid dynamics (CFD) is one of the computer-based solution methods which are more widely employed in aerospace engineering. The computational power and time required to carry out the analysis increases as the fidelity of the analysis increases. Aerodynamic shape optimization has become a vital part of aircraft design in the recent years. The Method of search algorithms or optimization algorithms is one of the most important parameters which will strongly influence the fidelity of the solution dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The airfoil structure significantly influences the energy efficiency of wind power generation Sharma, Gupta, Pandey, Sharma, & Mishra (2021) . Due to the high cost of CFD calculation Koziel & Leifsson (2013) , - The aerodynamic performance optimization Bedon et al (2016) ; Chen and Li (2019) ; Kallath et al (2021) ; Mukesh et al (2012) ; Saleem and Kim (2020) ; Tang et al (2017) and robustness optimization Reis et al (2019) of Airfoil Based on CFD are limited. Therefore, optimizing the efficiency of airfoil structures has been a focus of research community.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The airfoil structure significantly influences the energy efficiency of wind power generation Sharma, Gupta, Pandey, Sharma, & Mishra (2021) . Due to the high cost of CFD calculation Koziel & Leifsson (2013) , - The aerodynamic performance optimization Bedon et al (2016) ; Chen and Li (2019) ; Kallath et al (2021) ; Mukesh et al (2012) ; Saleem and Kim (2020) ; Tang et al (2017) and robustness optimization Reis et al (2019) of Airfoil Based on CFD are limited. Therefore, optimizing the efficiency of airfoil structures has been a focus of research community.…”
Section: Introductionmentioning
confidence: 99%
“…Mukesh et al studied the performance of different optimization algorithms, such as GA and PSO based on CFD. The authors concluded that as compared with other methods, the PSO method has a greater ability to find the global optimal value Mukesh et al (2012) . Chen et al further fused the GA and PSO to optimize the NACA0018 wing sail and obtained a larger thrust than the original wing Chen and Li (2019) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations